2007
DOI: 10.1136/vr.161.8.265
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of voriconazole in falcons

Abstract: Doses of 12.5 mg voriconazole/kg bodyweight administered every 12 hours by crop gavage to six falcons for 14 days provided peak plasma concentrations of more than 1 microg/ml, but the trough concentrations were lower and sometimes undetectable. Administering the same doses incorporated into meat that was fed to one falcon for seven days and to three falcons for up to 91 days provided similar plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Dose not mentioned Voriconazole Oral 10 mg/kg q12 h (pigeon) (Beernaert et al, 2009a,b), q24 h (chickens) (Burhenne et al, 2008) (African grey parrots) (Scope et al, 2007) 12 to 18 mg/kg q12 h (African grey parrots) (Flammer & Orosz, 2008) 12.5 mg/kg q12 h, 3 days loading dose, then q24 h (raptors) Schmidt et al, 2007) 40 mg/kg q24 h (quails) (Tell et al, 2009) 5-fluorocytosine Oral 50 to 100 mg/kg q12 h (Flammer, 1993) 60 to 250 mg/kg q12 h (cage birds); 40 mg/kg q6 to 8 h (raptors) (Jenkins, 1991) 150 to 250 mg/kg q12 h 21 days (Bauck et al, 1992) 120 mg/kg q12 h 3 weeks (Westerhof, 1995) 75 to 120 mg/kg q24 h (dose/4 q6 h) (Redig & Duke, 1985) 120 mg/kg q6 h (Joseph et al, 1994) a Every.…”
Section: Antifungal Agent Administration Route Dosementioning
confidence: 99%
“…Dose not mentioned Voriconazole Oral 10 mg/kg q12 h (pigeon) (Beernaert et al, 2009a,b), q24 h (chickens) (Burhenne et al, 2008) (African grey parrots) (Scope et al, 2007) 12 to 18 mg/kg q12 h (African grey parrots) (Flammer & Orosz, 2008) 12.5 mg/kg q12 h, 3 days loading dose, then q24 h (raptors) Schmidt et al, 2007) 40 mg/kg q24 h (quails) (Tell et al, 2009) 5-fluorocytosine Oral 50 to 100 mg/kg q12 h (Flammer, 1993) 60 to 250 mg/kg q12 h (cage birds); 40 mg/kg q6 to 8 h (raptors) (Jenkins, 1991) 150 to 250 mg/kg q12 h 21 days (Bauck et al, 1992) 120 mg/kg q12 h 3 weeks (Westerhof, 1995) 75 to 120 mg/kg q24 h (dose/4 q6 h) (Redig & Duke, 1985) 120 mg/kg q6 h (Joseph et al, 1994) a Every.…”
Section: Antifungal Agent Administration Route Dosementioning
confidence: 99%
“…27,29 Nonetheless, the efficacy of VCZ with natural and/or experimental aspergillosis has been reported in falcons, a red-tailed hawk, Japanese quail, and domestic pigeons with effective treatment achieved at an every 12 hour interval. 28,31,32,35,36 Burhenne et al showed in their long-term study in chickens that tissue distribution of VCZ was adequate, so the authors concluded that the oral dosage of 10 mg/kg likely produces effective concentrations against A. fumigatus in most peripheral compartments and tissues, even 12 hours after administration. 30 This effect was not seen in the lung tissue of pigeons that were tested 12 hours after administration.…”
Section: Birdsmentioning
confidence: 96%
“…25,26 The pharamacokinetics of vorioconazole have been evaluated in Mallard ducks Amazon parrots (Amazona ventralis). 27,28,29,30,31,32,33,34 Oral bioavailability has been established in Mallard ducks, chickens, and pigeons at 61, 16, and 44%, respectively 27,30,32 ; it is unclear why this level is so much lower than humans (>90%).…”
Section: Birdsmentioning
confidence: 98%
See 2 more Smart Citations